2226. Immune Checkpoint Inhibitors in Solid Tumor Patients with Chronic Hepatitis C Virus Infection: A Prospective Case-Series. (26th November 2018) - Hosry, Jeff; Naing, Aung; Torres, Harrys
Abstract: Background: Immune checkpoint inhibitors are a novel class of targeted therapy that activates T cell-mediated tumor cell death. Controversies exist about the safety and efficacy of immunotherapy in patients with chronic viral infections affecting T cells, such as hepatitis C virus (HCV). Herein, we analyzed the effect of immune checkpoint inhibitors on HCV viremia and HCV-related hepatic outcome. Methods: HCV-infected patients with solid tumors seen at MD Anderson Cancer Center (November 2012–April 2018) were enrolled in a prospective observational study. Patients were monitored for the development of HCV reactivation (HCV-RNA ≥1 log10 IU/mL over baseline), hepatitis flare (alanine transaminase increase to ≥3 times upper limit of normal) and HCV-associated hepatitis (HCV reactivation and hepatitis flare) while on cancer treatment. Results: Out of 205 chronically infected patients with solid tumors, 12 (6%) received immunotherapy and were seen in the HCV clinic, but only four (2%) returned for regular monitoring (Table 1). They were followed for 9 months. None of the four patients received concomitant chemotherapy or steroids. Hepatitis flare occurred in three patients, but HCV reactivation or HCV-associated hepatitis was not detected in any study patient. Immune checkpoint inhibitors were discontinued in one patient (25%) due to hepatitis flare unrelated to HCV. Conclusion: The use of immune checkpoint inhibitors appears to be safe in solid tumor patients with HCV infection. Disclosures: H. Torres, Gilead Sciences, Merck & Co., Inc.: Grant Investigator, Grant recipient. Vertex Pharmaceuticals: Grant Investigator, Grant recipient.